PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA TOKO EVA FASHION DESA PETUMBUKAN KECAMATAN GALANG KABUPATEN DELI SERDANG - Nur Hafni Maulida Nasution; Sari Wulandari (JURNAL MUTIARA MANAJEMEN, 2021)
The purpose of this study was to analyze the effect of product quality (X) on customer loyalty (Y) at the Eva Fashion Store, Petumbukan Village, Galang District, Deli Serdang Regency. The population of the study was the customers in Eva Fashion Store, Petumbukan Village, Galang District, Deli Serdang Regency as many as 160 customers for 1 week. The number of samples to be taken in this study if rounded is 62 samples. The data collection technique used is by using interviews (interviews), questionnaires (questionnaires) and observations (observations). given to respondents. Data using SPSS 20. The results of this study indicate that based on the simple regression test (a) of 6.008 while the simple regression coefficient (b) of 0.926 and it can be concluded that Product Quality has a positive influence on Customer Loyalty, which means that if the Product Quality increases then Customer Loyalty will increase by 0.926. Based on the t test, it is known that tcount > ttable is 11,679 > 2,000. So it can be said that product quality has a significant effect on customer loyalty at the Eva Fashion Store, Petumbukan Village, Galang District, Deli Serdang Regency. From the results of the coefficient of determination (R Square) it can be said that the product quality variable (X) has an influence on the Customer Loyalty variable (Y) of 69.5% and the remaining 30.5% is influenced by other variables outside of this study.